Molecular characterisation of Cryptococcus neoformans and Cryptococcus gattii present in tree hollows, their antifungal susceptibility, and chemical factors influencing their growth on woody debris - Vreulink, Jo-Marie (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.